Influence of wearing an unstable shoe construction on compensatory control of posture - Andreia S. P. Sousa (2013)
This study investigated the influence of wearing unstable shoe construction (WUS) on compensatory postural adjustments (CPA) associated with external perturbations. Thirty-two subjects stood on a force platform resisting an anterior-posterior horizontal force applied to a pelvic belt via a cable, which was suddenly released. They stood under two conditions: barefoot and WUS. The electromyographic (EMG) activity of gastrocnemius medialis, tibialis anterior, rectus femoris, biceps femoris, rectus abdominis, and erector spinae muscles and the center of pressure (Cop) displacement were acquired to study CPA. The EMG signal was used to assess individual muscle activity and latency, antagonist co-activation and reciprocal activation at joint and muscle group levels. Compared to barefoot, WUS led to: (1) increased gastrocnemius medialis activity, (2) increased total agonist activity, (3) decreased antagonist co-activation at the ankle joint and muscle group levels, (4) increased reciprocal activation at the ankle joint and muscle group levels, and (5) decrease in all muscle latencies. No differences were observed in CoP displacement between conditions. These findings demonstrate that WUS led to a reorganization of the postural control system associated to improved performance of some components of postural control responses.